Studies of the energy source for hydromagnetic waves at auroral latitudes - Tonegawa, Y.; Fukunishi, H.; Lanzerotti, L.J.; Maclennan, C.G.; Medford, L.V.; Carpenter, D.L. (1985)
P(論文) A preliminary report is given of a study of hydromagnetic waves observed on the ground at a high latitude (South Pole) location and at a station in the auroral zone (Syowa Station) during a day with considerable magnetic activity at ƒ∿30mHz. South Pole Station was located on closed field lines throughout the local day time interval of interest. Through cross-correlation spectral analyses, it is concluded that an external wave energy source can be observed over a wider azimuthal extent at an auroral zone location than at a location close to the magnetopause. The observations on this day at the two locations are studied for possible harmonic structure in the excited wave bands. It is suggested that such harmonic structure exists at the auroral zone station, but it is not clear at the South Pole Station. departmental bulletin paper